2020
DOI: 10.1002/adfm.202000922
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Ice Template Approach to Fabricate 3D Flexible MXene Film‐Based Electrode for High Performance Supercapacitors

Abstract: MXenes with metallic conductivity, high pseudo-capacitance and 2D structure, are promising flexible electrode materials for supercapacitors, but suffer from the restacking issue, which hinders ion accessibility and causes sluggish ion kinetics. Herein, a simple in situ ice template strategy is proposed to fabricate free-standing, flexible 3D porous Ti 3 C 2 T x /carbon nanotubes (CNTs) film (3D-PMCF) by freeze-drying Ti 3 C 2 T x-based hydro-films without any postprocessing. During the freeze-drying process, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
163
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 239 publications
(176 citation statements)
references
References 62 publications
2
163
0
Order By: Relevance
“…[30] Ice-templating has been employed to develop high-performance supercapacitor films with MXene, such as in the work demonstrated by Zhang Peng et al which showcases a Ti 3 C 2 T x /CNT film with an internal porous network, exposing a greater amount of surface active sites. [31,32] FaTC is a popular manufacturing method for functionally graded structures and porous ceramics. [33][34][35][36][37][38] For example, Yu Chen et al [33] fabricated functionally graded acicular electrodes for solid oxide fuel cells using this method, achieving enhanced electrochemical performance.…”
Section: Introductionmentioning
confidence: 99%
“…[30] Ice-templating has been employed to develop high-performance supercapacitor films with MXene, such as in the work demonstrated by Zhang Peng et al which showcases a Ti 3 C 2 T x /CNT film with an internal porous network, exposing a greater amount of surface active sites. [31,32] FaTC is a popular manufacturing method for functionally graded structures and porous ceramics. [33][34][35][36][37][38] For example, Yu Chen et al [33] fabricated functionally graded acicular electrodes for solid oxide fuel cells using this method, achieving enhanced electrochemical performance.…”
Section: Introductionmentioning
confidence: 99%
“…[113][114][115][116][117][118][119] The synergistic effects are expected for 2D MXene/1D nanomaterial heterostructures to combine both structural advantages of 1D nanostructure and 2D MXene for desirable performances. [32,33,54,[66][67][68][69][120][121][122] For example, Xiao et al [66] anchored well-defined CdS nanorods on ultrathin Ti 3 C 2 T x nanosheets through electrostatically driven assembly and hydrothermal methods (Figure 6a). The SEM image shows that CdS nanorods are tightly anchored on the surface of 2D MXene Ti 3 C 2 T x nanosheets ( Figure 6b).…”
Section: (10 Of 32)mentioning
confidence: 99%
“…© 2020 Wiley-VCH GmbH or MXenes incorporated into heterostructures is a decisive strategy. [32,34,49,83,[175][176][177] In 2018, Yoon et al [83] reported that an N-doped Ti 2 CT x with different N doping contents was successfully synthesized by sequential intercalation and decomposition of carbon nitride through a simple exfoliation and thermal annealing method. The cyclic voltammetry (CV) curves for pristine Ti 2 CT x , N-doped Ti 2 CT x at 500 °C, N-doped Ti 2 CT x at 700 °C, N-doped Ti 2 CT x at 900 °C, and Ti 2 CT x at 900 °C without NH 2 CN in 6 m KOH electrolyte at a scan rate of 100 mV s −1 exhibit that the CV curve shape of N-doped Ti 2 CT x becomes more and more rectangular as the annealing temperature increases, and its corresponding areas also become larger (Figure 10a).…”
Section: (16 Of 32)mentioning
confidence: 99%
See 1 more Smart Citation
“…Since they were firstly reported in 2011, MXenes have attracted much attention due to their unique structure and surface chemistry [ 2 , 3 ]. Especially for the application in supercapacitors, MXenes are promising electrode materials because they exhibit much higher pseudocapacitance, larger density and metallic conductivity compared with carbon materials used in the conventional electric double layer capacitors (EDLCs) [2][3][4][5][6] . Furthermore, with the 2D lamellar structure, MXenes can be fabricated into flexible and freestanding electrodes without current collector and binder, implying great potential in flexible energy storage devices [ 1 , 7-10 ].…”
Section: Introductionmentioning
confidence: 99%